Finite element prediction of the axial load test on the profiled composite panel - Chong, Pei Shan (2010)
The usage of composite structure has been run for a long time in construction industry and its have become more popular to civil engineers. Profiled steel sheeting structures are getting famous because its stiffness, strength and faster the construction period. The objective of this project is to analyse the behaviour of profiled composite panel under axial load by using finite element method. Foam concrete, Spandek and Trimdek profiled steel sheeting panel are used as composite material and the dimension of panels are set as 700 - 760 mm width with 1000 mm height and 85mm thickness. There are six types of models have been analyses in this project. LUSAS Modeller 14.0 Finite Element Software is able to carry out linear analysis to determine the deformed mesh, maximum stress and strain under axial load condition. in addition, critical buckling load can be predicted under the linear eigenvalue analysis. It concludes that Spandek Profiled Composite Panel can sustain higher buckling load than Trimdek Profiled Composite Panel.